PERAN PENYULUH PERTANIAN TERHADAP HASIL PRODUKSI PADI SAWAH DI DESA CIBUNIASIH KECAMATAN PANCATENGAH KABUPATEN TASIKMALAYA - Soni Ariana; Ristina Siti Sundari; Dona Setia Umbara (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Extension is a non-formal learning process to provide knowledge, training, technology, capital, and change the behavior of farmers to be more independent in making decisions. The role of the extension agent in extension activities is as a guide, organizer, technician and consultant to help farmers develop farming and increase production. This study aims to determine the effect of the role of agricultural extension workers on the production of lowland rice in Cibuniasih Village. The research method used is a survey and interviews with 68 respondents, namely rice farmers in Buniasih Village, then analyzed using multiple linear regression. The results showed that the role of agricultural instructors had a significant effect of 66.6% on rice production in Cibuniasih Village. The role of agricultural instructors as supervisors and consultants has a significant influence on the results of lowland rice production, meaning that the performance of extension workers in mentoring and consulting activities with farmers is going well. However, the role of agricultural extension workers as organizers and technicians has not had a significant effect on rice production, because the introduction of technology is still not appropriate and the needs of farmers have not been met properly.